A cluster-randomized, placebo-controlled trial to evaluate the efficacy of a spatial repellent - Tissera, Hasitha; Dheerasinghe, D. S. Anoja F; Malavige, Neelika; de Silva, H. Asita; Morrison, Amy C; Scott, Thomas W; Reiner, Robert C; Grieco, John P; Achee, Nicole L (Trials, 2023)
Background Spatial repellents (SRs) have been widely used for prevention of mosquito bites, but their efficacy in reducing Aedes-borne viruses (ABV) has not been tested rigorously at large scale in Asia. To address this knowledge gap, a trial to evaluate the efficacy of Mosquito Shield[TM], a transfluthrin SR, was developed in Gampaha District of Sri Lanka across three Medical Officer of Health areas; i.e., Negombo, Wattala, and Kelaniya. Methods This trial is a cluster-randomized, placebo-controlled, double-blinded clinical trial. A total of ~14,430 subjects aged [greater than or equal to] 6 months in 30 clusters (15 intervention, 15 placebo) from ~3900 households (HH) will be randomly selected for enrolment into a "febrile surveillance cohort." A subset of the surveillance cohort, ~3570 subjects aged [greater than or equal to]4-16 years that test seronegative (naïve) or are serologically positive for a previous single dengue virus (DENV) infection (monotypic) at baseline sampling, will be enrolled into a "longitudinal cohort" for measuring DENV infection based on laboratory-confirmed seroconversion during the trial. Persons identified positive for antibodies against multiple DENV serotypes (multitypic) at baseline will be monitored for secondary analyses. Active ABV disease will be assessed using an enhanced passive surveillance system with case ascertainment performed in designated healthcare facilities. Serum samples will be taken from longitudinal cohort subjects within 1-2 weeks of when intervention is first deployed (T0) with additional samples taken ~12 (T1) and ~24 months (T2) from baseline sampling. DENV seroconversion and ABV active disease rates from baseline (pre-intervention) and follow-up (post-intervention) samples will be compared between intervention and placebo clusters. Participating houses will be monitored entomologically (indoor adult Aedes aegypti population densities and adult female blood fed status) within 3 months before intervention deployment and monthly during the intervention phase. Entomological surveys will monitor indoor adult Ae. aegypti population densities and blood fed status. Dengue incidence in each cohort will be estimated and compared to determine the public health benefit of using an SR. Entomological parameters will be measured to determine if there are entomological correlates of SR efficacy that may be useful for the evaluation of new SR products. Discussion The trial will serve as an efficacy assessment of SR products in South Asia. Results will be submitted to the World Health Organization Vector Control Advisory Group for assessment of public health value towards an endorsement to recommend inclusion of SRs in ABV control programs. Trial registration Sri Lanka Clinical Trial Registry SLCTR/2022/018. Registered on July 1, 2022. ClinicalTrials.govNCT05452447. Registered on July 11, 2022. The Universal Trial Number is U1111-1275-3055. Keywords: Spatial repellent, Dengue, Aedes-borne Viruses, Transfluthrin, Incidence, Cluster-randomized controlled trial, Sri Lanka